PENGARUH CITRA DAN STORE ATMOSPHERE TERHADAP KEPUASAN PELANGGAN - SULFIANTI, SULFIANTI (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2015)
This study aims to find and analyze: (1) Significant influence of image and store atmosphere variable to customer satisfaction RM Radja Penyet Mas Fais Cab. Ahmad yani Palu, (2) The significant effect of image variable on customer satisfaction RM Radja Penyet Mas Fais Cab. Ahmad yani Palu, (3) Significant influence of store atmosphere variable to customer satisfaction RM Radja Penyet Mas Fais Cab. Ahmad yani Palu.The type of research used is causality (shows the relationship between variables). The populations that become the object in this study are the customers RM Radja penyet Mas Fais Cab.Ahmad Yani that can not be determined and unclear. Sampling technique in this study using purposive sampling, with the number of samples of 100 respondents. Data collection using questionnaires that have been tested for validity and reliability. The method of analysis using multiple regression analysis. The results showed (1) image and store significant atmosphere to customer satisfaction in RM Radja Penyet Mas Fais Cab. Ahmad Yani Palu, (2) Citra angry significant to customer satisfaction in RM Radja Penyet Mas Fais Cab. Ahmad Yani Palu, (3) Storing a significant response to customer satisfaction at RM Radja Penyet Mas Fais Cab. Ahmad Yani Palu.